FOUCAULT E HEIDEGGER: MESTRES DO CUIDADO - Medeiros, Claudio V. F. (2017)
Are the practices of subjectivation – including Michel Foucault's "arts of existence" – alternatives to an ethic entirely distinct from philosophical ethics based on an adequacy to the categories of a moral truth supported by human nature, by God's nature, by the contracts organized around the idea of "good" of sociability, by nature of sociability rules anticipated by the presuppositions of the communication? Through the comparison between Heidegger’s concept of "care", as a structure that preserves the openness of there-Being to the confrontation with his essential character of potentiality-for-Being, and the Foucault’s concept of “Care of the Self”, a kind of revitalization of philosophical practice that refers "education to politics" to a certain "self-relations to itself," we intend to introduce the characteristics of a philosophical ethic that was influenced by Heidegger in the tradition that constituted contemporary French philosophy.